2018
DOI: 10.3389/fcimb.2018.00397
|View full text |Cite
|
Sign up to set email alerts
|

Immunity Against Leishmania major Infection: Parasite-Specific Granzyme B Induction as a Correlate of Protection

Abstract: Zoonotic cutaneous leishmaniasis (ZCL) caused by Leishmania (L.) major infection is characterized by different clinical presentations which depend in part on the host factors. In attempt to investigate the impact of the host's immune response in the outcome of the disease, we conducted a prospective study of 453 individuals living in endemic foci of L. major transmission in Central Tunisia. Several factors were assessed at the baseline including (i) the presence of typical scars of ZCL, (ii) in vivo hypersensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…(43,44). Protection takes place by production of nitric oxide (NO) by the inducible NO synthase (iNOS) in macrophages in order to kill the amastigotes (45)(46)(47)(48).…”
Section: An Overview On Anti-leishmania Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…(43,44). Protection takes place by production of nitric oxide (NO) by the inducible NO synthase (iNOS) in macrophages in order to kill the amastigotes (45)(46)(47)(48).…”
Section: An Overview On Anti-leishmania Immunitymentioning
confidence: 99%
“…IFN-γ levels collectively produced by CD4 + Th1 and other activated cells types, such as CD8 + T cells and natural killer (NK) cells, is, so far, known as the best correlate of protection in leishmaniasis ( 43 , 44 ). Protection takes place by production of nitric oxide (NO) by the inducible NO synthase (iNOS) in macrophages in order to kill the amastigotes ( 45 48 ).…”
Section: An Overview On Anti-leishmania Immunitymentioning
confidence: 99%
“…GrB, is a proapoptotic protease that has been associated with both tissue damage and good prognosis in CL and VL patients [28-32, 95, 96]. It was recently reported that GrB constitutes a good correlate for protection against severe forms of CL [33].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…CD8+ T cells are also important in the healing mainly through IFN-γ production [24][25][26]. These cells have also been involved in pathogenesis, trough Granzyme B (GrB) production [27][28][29][30], while other studies showed that an increase of GrB activity was associated with a good prognosis in patients with CL [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the American tegumentary leishmaniasis also stimulates complex immune and inflammatory responses at local level in the skin with production of IL-4, IL-6 and IL-22 by cells Th17 [13,14]. However, the chronic mucous form of the infection is characterized by an immune response oriented towards Th2 favouring a persistent inflammation at local and/or systemic level [15,16,17].…”
Section: Introductionmentioning
confidence: 99%